(untitled) (The Batuk, 2025)
Parental conflict is a serious threat to children’s mental health because it undermines emotional security, behavioral regulation, and long-term psychological adaptation. This qualitative study looks at the effects of parental conflict on children by analyzing real-life cases of people aged eight to fifteen who have been subjected to ongoing familial strife. The findings show that exposure to verbal arguments, physical violence, and emotional neglect contributes to increased anxiety, depression, low self-esteem, and poor academic performance. Children frequently withdraw emotion, isolate themselves, and struggle to make new friends. In Nepal, where cultural norms and family hierarchies have a significant impact on how children grow up, being unable to discuss problems at home adds to the mental strain. The study demonstrates the importance of raising awareness, educating parents, and providing appropriate mental health services, such as school-based counseling and community support systems. It also demonstrates the importance of strengthening legal protections and using culturally sensitive conflict resolution methods. To protect children’s emotional health and promote healthier growth in families and communities, these issues must be addressed.